Investigating the complex relationships between nurses’ work factors, Sharia-based nursing care, and patient satisfaction in an Islamic hospital: A PLS-SEM approach - Iwan Ardian; Nursalam; Ahsan; Nutrisia Nuim Haiya; Intan Rismatul Azizah (Belitung Nursing Journal, 2023)
Background: Healthcare services in Islamic hospitals are becoming increasingly important due to the growing global Muslim population and the demand for spiritually sensitive healthcare. Understanding the factors contributing to patient satisfaction in this context is paramount. Objective: This research aimed to investigate the relationships between nurses’ work factors, Sharia-based nursing care, and patient satisfaction in an Islamic hospital in Indonesia. Methods: This study employed a cross-sectional design involving 260 respondents, comprising 130 patients and 130 nurses in inpatient rooms. Data collection took place in August 2022 at an Islamic Hospital in Indonesia using validated questionnaires. SmartPLS 3.2.8 was used to generate Partial Least Square Structural Equation Modeling (PLS-SEM) to assess and analyze relationships between research variables. Results: Nurses’ work factors had a significant impact on Sharia-based nursing care (β = 0.813, t = 18.582, p <0.001). Furthermore, Sharia-based nursing care had a significant influence on patient satisfaction (β = 0.509, t = 3.941, p <0.001), while nurses’ work factors had a moderately significant effect on patient satisfaction (β = 0.396, t = 3.079, p = 0.002). The interaction between work factors and Sharia-based nursing care had an influence on patient satisfaction (β = 0.366, t = 3.666, p <0.001), explaining 74.4% of the variance observed in patient satisfaction. Conclusion: This study offers valuable insights into the significance of improving nurses’ work factors, including elements such as performance, feedback, correction, and job design, along with the integration of Sharia-based principles in nursing care. The study suggests that nursing administrators, healthcare policymakers, and academic institutions should prioritize the creation of supportive work environments and culturally sensitive care practices for nurses to enhance patient satisfaction.